The Use of Radiation Therapy in Well-Differentiated Soft Tissue Sarcoma of the Extremities: An NCDB Review. (7th May 2015) - Lazarides, Alexander L.; Eward, William C.; Speicher, Paul J.; Hou, Chun-Han; Nussbaum, Daniel P.; Green, Cindy; Blazer, Dan G.; Kirsch, David G.; Brigman, Brian E.
Abstract : Objective . This study investigated patterns of utilization of radiation therapy (RT) and correlated this with overall survival by assessing patients with well-differentiated soft tissue sarcoma of the extremity (STS-E) in the National Cancer Database (NCDB). Methods . All patients diagnosed with well-differentiated STS-E between 1998 and 2006 were identified in the NCDB. Patients were stratified by use of surgery alone versus use of adjuvant RT after surgery and analyzed using multivariate analysis, Kaplan-Meier analysis, and propensity matching. Results . 2113 patients with well-differentiated STS-E were identified in the NCDB for inclusion with a mean follow-up time of 74 months. 69% of patients were treated with surgery alone, while 26% were treated with surgery followed by adjuvant RT. Patients undergoing amputation were less likely to receive adjuvant RT. There was no difference in overall survival between patients with well-differentiated STS treated with surgery alone and those patients who received adjuvant RT. Conclusions . In the United States, adjuvant RT is being utilized in a quarter of patients being treated for well-differentiated STS-E. While the use of adjuvant RT may be viewed as a means to facilitate limb salvage, this large national database review confirms no survival benefit, regardless of tumor size or margin status.